PERANAN KOMPETENSI SDM UMKM DALAM MENINGKATKAN KUALITAS KERJA UMKM KOTA TASIKMALAYA (Studi Kasus UMKM Batik Kota Tasikmalaya) - Barin Barlian (Business Education Program of Universitas Pendidikan Indonesia, 2022)
The aim of this research is to find out how the Competency of Human Resources of Batik UMKM in Tasikmalaya City and how the influence of UMKM Human Resources competence on the Work Quality of UMKM. The research method used is descriptive exploratory. The sample of respondents used in this study were 40 respondents which included owners and employees. The results of this study are as follows: Competency of HR of Small-Medium Entrepreneurs is in the good category and good competence of HR will certainly improve the quality of these SMEs.